Pathways for HIV Prevention Behaviors Following a Home-Based Couples Intervention for Pregnant Women and Male Partners in Kenya. - Hatcher, Abigail M.; Darbes, Lynae; Kwena, Zachary; Musoke, Pamela L.; Rogers, Anna Joy; Owino, George; Helova, Anna; Anderson, Jami L.; Oyaro, Patrick; Bukusi, Elizabeth A.; Turan, Janet M. (AIDS & Behavior, 2020)
Pregnancy is a time of heightened HIV risk, but also a phase when a couple can prioritize family health. We conducted secondary analysis of a home-based intervention in rural Kenya to explore couple-level adherence to HIV prevention behaviors. The intervention included health education, relationship-building skills, and Couples HIV Testing and Counseling. Pregnant women were randomized to the intervention (n = 64) or standard care (n = 63) along with male partners. Of 96 couples, 82 (85.0%) were followed to 3 months postpartum, when 31.0% of couples reported perfect adherence to HIV prevention. In logistic regression, intervention condition couples had three-fold higher odds of perfect adherence (AOR = 3.07, 95% CI = 1.01–9.32). A structural equation model found the intervention had moderate effects on couple communication, large effects on couple efficacy to take action around HIV, which in turn improved HIV prevention behaviors (CFI = 0.969; TLI = 0.955; RMSEA = 0.049). Strengthening couple communication and efficacy may help prevent the spread of HIV to infants or partners around the time of pregnancy.